Studies in symbolic interaction. Vol. 25 - Denzin, Norman K. (JAI, 2002)
This volume emphasizes interpretive interactionist work on race, media, culture and identity. Experimental, autoethnographic performance texts are privileged, as are recent theoretical developments in symbolic interaction theory involving critical humanism, pragmatic theories of power and the layered bureaucracy. It also presents essays on the New Iowa School, the work of Gideon. S. Joberg, cultural studies and symbolic interactionism, including the work of Norman Denzin.